2018
DOI: 10.1159/000493740
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate-Related Antibodies and Peripheral Insulin-Like Growth Factor in Bipolar Disorder and Lithium Prophylaxis

Abstract: Aims: The aim of this study was to evaluate serum levels of the antineuronal antibodies anti-N-methyl-D-aspartate receptor (NMDAR) and anti-glutamic acid decarboxylase (GAD), and insulin-like growth factor 1 (IGF-1), in patients with bipolar disorder (BD), during manic and depressive episodes and in remission compared to euthymic patients receiving long-term lithium therapy. Methods: Serum levels of anti-NMDAR and anti-GAD 450/620 antibodies, as well as IGF-1, were measured using the ELISA method in 19 manic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It seems that in female patients, longterm lithium administration may exert an immunomodulatory effect. In our recent study, we found significantly lower levels of antiglutamate antibodies (anti-NMDAR and anti-GAD) in lithium-treated bipolar patients compared to bipolar subjects during acute episode and immediate remission after the episode [15]. We also observed that long-term treatment with lithium might suppress the activation of regenerative processes by reducing the number of VSELs (very small embryonic-like stem cells) and attenuate inflammatory processes reflected by the higher expression of pluripotency and glial markers in the peripheral blood of bipolar patients [16].…”
Section: Lithium-treatedmentioning
confidence: 85%
“…It seems that in female patients, longterm lithium administration may exert an immunomodulatory effect. In our recent study, we found significantly lower levels of antiglutamate antibodies (anti-NMDAR and anti-GAD) in lithium-treated bipolar patients compared to bipolar subjects during acute episode and immediate remission after the episode [15]. We also observed that long-term treatment with lithium might suppress the activation of regenerative processes by reducing the number of VSELs (very small embryonic-like stem cells) and attenuate inflammatory processes reflected by the higher expression of pluripotency and glial markers in the peripheral blood of bipolar patients [16].…”
Section: Lithium-treatedmentioning
confidence: 85%
“…In particular, the rapid cycling BD subtype is associated with thyroidperoxidase-antibodies ( Snijders et al., 2019 ). Serum levels of antibodies such as NMDAR antibodies also play a key role in the development of an acute manic, untreated mood state ( Ferensztajn-Rochowiak et al., 2019 ). Surprisingly, mania-like symptoms such as euphoria may often be the first symptom in patients with NMDAR encephalitis, as indicated in a recent study by Restrepo-Martinez (2019), thus screening for NMDAR-antibodies is clinically relevant in patients presenting an acute onset of mania combined with a psychopathology characterized by a strong sense of delight and a lack of inhibition.…”
Section: Psychiatric Symptoms and Syndromes Associated With Autoantibodiesmentioning
confidence: 99%
“…Although ASD and other neurodevelopmental disorders are not typically considered as autoimmune diseases, autoantibodies, or antibodies that bind to self-antigens, have been detected in the sera of patients with ASD, ADHD, bipolar affective disorder and schizophrenia (22). Autoantibodies against known targets have been linked to the development of behavioral symptoms in these disorders, for example anti-dopamine transporter autoantibodies have been related with severity and recovery in ADHD, antibodies against myelin basic protein (MBP) have higher titers in patients with negative symptoms in schizophrenia or N-methyl-D-aspartate receptor (anti-NMDAR) and glutamic acid decarboxylase (anti-GAD) antibodies have been associated with acute maniac episodes in bipolar disorder (2325). The best-studied example are autoantibodies directed against the NMDAR in a condition known as anti-NMDAR encephalitis, characterized by the development of psychosis, cognitive problems and seizures.…”
Section: Introductionmentioning
confidence: 99%